PECULIARITIES OF CLINICAL TREATMENT, DIAGNOSTICS AND APPROACHES TO PAPILLOMA VIRAL THERAPY IN CHILDHOOD - L.P. Mazitova; L.K. Aslamazyan; L.S. Namazova; T.S. Shaipov (Педиатрическая фармакология)
In recent years, human papillomavirus infection in childhood is an urgent problem in the practice of doctors of various specialties. The urgency of the problem is due to the widespread presence of the nosology, the difficulties of the therapy, the frequent recurrence of the disease. In addition, the pathogenesis of this disease in children is poorly understood, the optimal algorithm of examination of this group of patients is not defined which makes the therapy irrational and provides the lack of primary and secondary prevention methods.Keywords: papillomavirus, diagnosis, treatment, children.